1969
DOI: 10.1111/j.1748-1716.1969.tb04379.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hypercapnia and Hypocapnia upon the Cerebrospinal Fluid Lactate and Pyruvate Concentrations and upon the Lactate, Pyruvate, ATP, ADP, Phosphocreatine and Creatine Concentrations of Cat Brain Tissue

Abstract: The lactate and pyruvate concentrations in cisternal cerebrospinal fluid (CSF), and the lactate, pyruvate, ATP, ADP, phosphocreatine, and creatine concentrations in brain tissue were measured in cats during hyper‐ and hypocapnia. (PaCO2 10–100 mm Hg). Both the CSF and the tissue concentrations of lactate and pyruvate varied inversely with the arterial CO2 tension. In hypercapnia the tissue lactate/pyruvate ratio increased in accordance with a theoretical curve, calculated for a pH dependent equilibrium between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1

Year Published

1973
1973
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(27 citation statements)
references
References 33 publications
5
21
1
Order By: Relevance
“…Cerebral venous oxygen tension was elevated in our experiments (Table III) and is usually related closely to cerebral blood flow as measured by xenon-133 clearance (13). Although Plum and Posner (15) and others (16)(17)(18) have found that passive hyperventilation may lead to decreased cerebral blood flow and increased CSF lactate, this association was not observed (17) at Pco2 values as high as those we observed in the presence of increased CSF lactate (Table I). Another possible source of increased lactic acid production is the phagocytosing inflammatory cells in the meninges (19).…”
Section: Respiration and Circulation In Meningitiscontrasting
confidence: 50%
“…Cerebral venous oxygen tension was elevated in our experiments (Table III) and is usually related closely to cerebral blood flow as measured by xenon-133 clearance (13). Although Plum and Posner (15) and others (16)(17)(18) have found that passive hyperventilation may lead to decreased cerebral blood flow and increased CSF lactate, this association was not observed (17) at Pco2 values as high as those we observed in the presence of increased CSF lactate (Table I). Another possible source of increased lactic acid production is the phagocytosing inflammatory cells in the meninges (19).…”
Section: Respiration and Circulation In Meningitiscontrasting
confidence: 50%
“…The elevation of the L=P in the brain is considered a reliable indicator of cerebral ischemia (Granholm and Siesjo, 1969;Persson and Hillered, 1992;Enblad et al, 1996). The L=P is elevated, at least in the early course of sTBI, as an indicator of brain injury and a compromised microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…The specific aim of the study was to establish whether the treatment with low-dose epoprostenol would reduce a L=P as measured by cerebral microdialysis after 24 h of treatment. The L=P is considered the most reliable marker for the redox state of the brain (Granholm and Siesjo, 1969;Persson and Hillered, 1992;Enblad et al, 1996). Secondly, the changes in microdialysis parameters over time in the epoprostenol and placebo groups were studied.…”
Section: à=àmentioning
confidence: 99%
“…3 -*• 23,24 According to MacMillan and Siesjo's observations, 23 cerebral lac tate in rats was increased to 3.42 mM/kg at paC0 2 21.1 mmHg and 5.25 mM/kg at paC0 2 …”
Section: Cerebral Blood Flowmentioning
confidence: 99%